Physical Activity Levels in Irish School Children - Carrier, Laurie; Herbert, Lara; Allen, Hilary; McChesney, William; O’Connor, Catherine; O’Kane, Anna (Trinity Student Medical Journal, 2003)
Objectives: This study aimed to assess the number of hours of physical activity engaged in by Irish school children per week, and compare them with the American Heart Association's recommendations. Both hours of physical activity per week and hours of television viewed per week were compared with sex, age and school location. Methods and Patients: Questionnaires were distributed to 9 co-educational schools (3 rural, 3 inner- city, 3 suburban). Irish school children (173 males and 116 females) between the ages of 10 and 12 years and 15 and 17 years participated. Results: Results showed that 81% percent of boys and 75% of girls met the criteria set by the American Heart Association regarding physical activity. Urban girls reported more physical activity than rural girls. Younger boys reported more physical activity than older boys while younger girls reported more physical activity than older girls. Finally, older girls also reported significantly less physical activity than older boys. The Irish school children surveyed watch an average of 15.5 hours of television per week. Boys attending urban schools reported watching less television than boys attending rural schools. Younger boys reported watching more television than older boys and suburban boys reported less television watching than boys in inner city schools. Conclusion: Older girls and rural school children appear to be particularly vulnerable to the development of sedentary rather than active lifestyles. This may provide two target groups for interventions to increase activity.